"Snoopy is the hero in Vietnam:" ambivalence, empathy, and Peanuts' Vietnam war. Issue 1 (2nd January 2016) - Ball, Blake Scott
Abstract: This article reconsiders the work of cartoonist Charles M. Schulz within the political context of the Vietnam War era. During the late Sixties, Peanuts became the most widely read comic strip in American history. Many assumed the strip was popular because it was inoffensive and avoided controversial topics. Far from apolitical or escapist, however, the strip subtly – and, at times, explicitly – engaged with serious national debates about such topics as the Vietnam War and the draft. Snoopy's daydreams of warfare as the Flying Ace became the vehicle for many of Schulz's musings on war and society. Schulz's personal experience as a drafted soldier in World War II led him to empathize with American troops in Vietnam, oppose the draft, and, yet, reluctantly support a war he increasingly hated. While he used Snoopy and the Peanuts gang to express his personal feelings about Vietnam, readers, commentators, and Vietnam soldiers appropriated the image of the Flying Ace to communicate their own feelings about the war. Thus, this article finds that Snoopy as the World War I Flying Ace became a significant, if underappreciated, part of Americans' Vietnam War iconography.